Trajetórias de formação e prática docente nas memórias de professoras leigas do Sertão Paraíbano (1970 a 1980) - Alves, Rozilene Lopes de Sousa (2023)
Studies on the History of Brazilian Education have significantly highlighted the need to develop investigations focused on the history and memory of teachers and educational institutions. From this perspective, the present research has as its object of study the understanding of how the initial and continued training and practice of lay teachers who worked in the first four grades of primary education in schools in the Sertão Paraibano took place, between the 1970s and 1970s. and 80s of the 20th century. It is therefore part of the History of Education Research Line of the Graduate Program in Education at the Federal University of Sergipe. In this perspective, the general objective of the work is to understand, through memories of oral expression, how the training and practice of lay teachers who worked in the first four grades of primary education in schools in the Sertão Paraibano took place, between the decades of 70s and 80s of the 20th century. Specifically, it aims to show, from the narratives of collaborating teachers, the reason for choosing the teaching profession; to inventory the institutions and training paths of these teachers for the exercise of teaching; understand the didactic-pedagogical postures assumed by the collaborators in the exercise of teaching as lay teachers and after the training acquired for the exercise of teaching in the 1st grade. For a better delineation of the conceptual and methodological bases of the work, research was carried out on dissertations and theses that address the history of the teaching profession inscribed in the training and practice trajectories of lay teachers between the 70's and 80's of the 20th century. From this perspective, the theoretical framework adopted has as its main foundations studies on History and Memory, based mainly on the ideas of Burke (1992), Le Goff (1998), Bosi (1994). It outlines historical aspects of teacher training in Brazil, based on Guiraldelli Júnior (2006), Saviani (2009), Tanuri (2000), among other studies. It addresses the training and performance of teachers in the state of Paraíba, based on Andrade (1995), Araújo (2010), Gouveia (2019), Pinheiro (2002). The methodological basis for data collection and analysis is based on the perspective of Narrative Research, with special attention to the thematic oral history proposed, mainly, by Meihy & Seawright (2020). The main source for data collection was the oral narrative through recorded interviews with the teachers who collaborated in the research and transcribed, posteriori, for the necessary analysis. Other sources were also used in order to expand the analytical look, intersecting with the subjects' narratives in order to contextualize the speeches, such as official documents and private collections, such as photographs and work materials. The study of the teaching career, through the delimitation of the study that we present here, allowed us to understand how the formation and professional performance of lay teachers from the Sertão of Paraíba took place between the decades of the 70s and 80s of the 20th century. We found that the stories experienced in regional and local education by the collaborators of this research, when analyzed in the intersection with Brazilian educational history, allow us to reflect on teacher training and performance throughout the history of Brazilian education.